1986
DOI: 10.1099/0022-1317-67-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Gangliosides in Rabies Virus Infection

Abstract: SUMMARYThe role of gangliosides in rabies virus infection of chick embryo-related (CER) cells was investigated. Cultured cells were pretreated with neuraminidase to render the cells transiently non-susceptible to viral infection. Incubation of these desialylated cells with gangliosides allowed them to incorporate exogenous gangliosides and they recovered their susceptibility to rabies virus infection. Infection of CER cells was monitored by specific fluorescence 24 h after virus inoculation. The use of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 40 publications
2
39
0
2
Order By: Relevance
“…In earlier reports we demonstrated that the lysosomal entry pathway is involved in the infection of non-neuronal cells as well as neurons Tsiang & Superti, 1984). Furthermore highly sialylated gangliosides may participate in these early steps of viral entry into the target cell (Superti et al, 1986;Conti et al, 1988). From our present results we infer that there are presumably two different mechanisms of viral entry into the cell.…”
Section: Retrograde and Anterograde Transport Of Rabies Virus In A Musupporting
confidence: 31%
See 1 more Smart Citation
“…In earlier reports we demonstrated that the lysosomal entry pathway is involved in the infection of non-neuronal cells as well as neurons Tsiang & Superti, 1984). Furthermore highly sialylated gangliosides may participate in these early steps of viral entry into the target cell (Superti et al, 1986;Conti et al, 1988). From our present results we infer that there are presumably two different mechanisms of viral entry into the cell.…”
Section: Retrograde and Anterograde Transport Of Rabies Virus In A Musupporting
confidence: 31%
“…Rabies virus infects a great variety of neuronal cell lines (Clark, 1978;Honda et al, 1984;Iwasaki & Clark, 1977;Tsiang et al, 1983a) as well as primary dissociated neuron cultures (Lycke & Tsiang, 1987;Tsiang et al, 1983aTsiang et al, , b, 1986. Whereas conventional neuronal cultures are less appropriate for the investigation of viral transport, neurons cultivated in a compartmentalized culture system as described by Campenot (1977) will demonstrate convincingly the transport of herpes simplex virus in vitro (Kristensson et al, 1986;Lycke et al, 1984;Ziegler & Herman, 1980) and the retrograde transport of both fixed and street rabies viruses in cultured rat sensory neurons (Lycke & Tsiang, 1987;Tsiang, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides, principally GD1b, GQ1b, and GT1b, have also been proposed to play a role in RV binding (48). While some of these gangliosides are prevalently found in subpopulations of DRG neurons, none have the specific expression pattern that is found in infected neurons (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of VSV, although phosphatidylserine has been considered to be the viral receptor for a long time [17], recent results indicated that it is not [18]. In the case of RV, many molecules, including gangliosides [19], phospholipids [20], the nicotinic acetylcholine receptor [21,22], neuronal cellular adhesion molecules [23] and the low-affinity nerve growth factor receptor [24], have been proposed to be viral receptors. After binding, the virions enter the cell by the endocytic pathway.…”
Section: Rhabdovirus Glycoprotein Gmentioning
confidence: 99%